CSTF2 Promotes Hepatocarcinogenesis and Hepatocellular Carcinoma Progression via Aerobic Glycolysis - Chen, Zhimin; Hao, Weijie; Tang, Jingzhi; Gao, Wei-Qiang; Xu, Huiming (Frontiers in Oncology, 2022)
Background The shortening of 3’ untranslated regions (3’UTRs) of messenger RNAs(mRNAs) by alternative polyadenylation (APA) is an important mechanism for oncogene activation. Cleavage stimulation factor 2 (CSTF2), an important regulator of APA, has been reported to have a tumorigenic function in urothelial carcinoma of the bladder and lung cancers. However, the tumor-promoting role of CSTF2 in hepatocellular carcinoma (HCC) and its underlying molecular mechanism remains unclear. Methods Multiple databases were used to analyze the expression level and prognostic value of CSTF2 in HCC. Function enrichment analysis was used to investigate the molecular mechanism of CSTF2 for the occurrence and development of HCC. The biological function in HCC cell lines in vitro was determined by CCK8, colony formation, Transwell migration, and invasion assay. Moreover, the tumorigenic function of CSTF2 in vivo was measured by a subcutaneous tumor formation or injecting four plasmids into a mouse tail vein within 5–7 s in an immunocompetent HCC mouse model. In addition, aerobic glycolysis in HCC cells was determined by measuring the extracellular acid rate (ECAR) and extracellular glucose and lactate levels. Results Bioinformatics analysis revealed that CSTF2 was overexpressed in HCC tissues. The high expression of CSTF2 was correlated with a poor prognosis and high histological grades. CSTF2 knockout inhibited the proliferation, migration, and invasion of HCC cells. In addition, CSTF2 knockout HCC cells failed to form tumors by a subcutaneous graft experiment. Furthermore, endogenous CSTF2 knockout attenuated hepatocarcinogenesis in an immunocompetent HCC mouse model. Function enrichment analysis suggested that the high expression of CSTF2 was associated with enhanced glycolysis. Moreover, we found that CSTF2 knockout reduced the level of the short 3’ UTR isoform of hexokinase 2 and increased its level of long 3’UTR. Furthermore, CSTF2 knockout inhibited ECAR levels, glucose uptake, and lactate production. Conclusion Our results indicated that CSTF2 is highly expressed in HCC and is correlated with a poor prognosis and high histological grade. The knockout of CSTF2 inhibits the tumorigenesis and procession of HCC both in vitro and in vivo. Moreover, CSTF2 is associated with enhanced glycolysis. Therefore, this study suggests that CSTF2 might be a new prognostic biomarker and therapeutic target for HCC.